The Role of Land Transportation in The Economic Development of Underdeveloped Villages in West Seram Regency: Bridging Isolation - Yenny Latekay; Muspida; Hendri D Hahury (LP2M IAIN Palopo, 2026)
This study examines the role of land transportation infrastructure in the economic development of underdeveloped villages in West Seram Regency, with particular attention to household dynamics, gender dimensions, and social capital. Employing a descriptive qualitative approach, data were collected through semi-structured interviews, participatory observation, and document analysis in three underdeveloped villages in Elpaputih District: Ahiolo Village, Abio Village, and Watui Village. The findings indicate that severely deteriorated road conditions, the absence of public transportation, and high vulnerability to weather-related disruptions have resulted in geographic isolation that reinforces a high-cost economy. High logistics costs, ranging from 14-34% of household income, significantly reduce profit margins, constrain market access, and intensify dependence on subsistence-based economic activities. Further, gendered impacts are evident, as women disproportionately bear the burden of mobility constraints. At the same time, communities demonstrate resilience through gotong royong (mutual cooperation) and local innovations, such as the use of bamboo rafts. However, these adaptive strategies function as a form of “shock absorber” that unintentionally sustains the status quo of infrastructure failure rather than addressing its structural causes. Policy recommendations include accelerating infrastructure improvement through participatory approaches that leverage local social capital, developing multimodal transportation systems integrating land and river transport, and implementing gender-responsive interventions to enhance women’s economic access. This study concludes that without comprehensive structural interventions, these villages are likely to remain trapped in a locked-in subsistence economy.